1988
DOI: 10.1145/42411.42422
|View full text |Cite
|
Sign up to set email alerts
|

MIS careers—a theoretical perspective

Abstract: MIS personnel historically have exhibited a disturbingly high rate of turnover, and the job of the MIS manager is increasingly oriented to personnel and staffing problems. The MIS careers literature consistently suggests that what is needed to improve this situation is (1) more attention to formal career planning, and (2) the implementation of a dual career ladder system within the DP/IS organization. A look at the broader literature on organizational careers suggests that these suggestions may not in fact mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(71 citation statements)
references
References 27 publications
0
69
0
2
Order By: Relevance
“…Third, the stability of MIS employees' career orientations should be empirically examined. For example, the career stage model of Dalton, Thompson, and Price (1977) may be a useful framework for viewing the career development of MIS employees over time (Ginzberg & Baroudi, 1988). It would be useful to determine whether and how career orientations change as people pass through the four stages of Dalton et al's (1977) model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the stability of MIS employees' career orientations should be empirically examined. For example, the career stage model of Dalton, Thompson, and Price (1977) may be a useful framework for viewing the career development of MIS employees over time (Ginzberg & Baroudi, 1988). It would be useful to determine whether and how career orientations change as people pass through the four stages of Dalton et al's (1977) model.…”
Section: Discussionmentioning
confidence: 99%
“…It also serves as a useful information base for individuals contemplating career change and for organizations seeking to help individuals plan their careers (DeLong, 1982;. Ginzberg and Baroudi (1988) noted that building a dual career ladder was the most commonly recommended IS HRM solution in both the IS practitioner and research literatures. The dual career ladder allows an individual's career to progress in either technical or managerial directions.…”
mentioning
confidence: 99%
“…One example of this approach is the categorization of skills according to the theoretical constructs of organizational and functional learning (e.g., Nelson 1991). Another example is the use of the career anchor model to identify skills that shape an individual IT professional's career (e.g., Ginzberg and Baroudi 1988;Lash and Sein 1995;Josefek and Kauffman 2003). From our perspective, however, there are two drawbacks to using a theoretical foundation to define the skill sets a priori.…”
Section: Prior Researchmentioning
confidence: 99%
“…By so doing, firms can monitor employees' incentives and provide at least satisfactory career opportunities. Ginzberg and Baroudi suggested that the match between IS personnel's internal career anchors and perceived incentives determines an individual's career satisfaction or intent to leave [13].…”
Section: Background and Research Hypothesesmentioning
confidence: 99%